Higher Light Extraction Efficiency in Organic Light-Emitting Devices by Employing 2D Periodic Corrugation - Bai, Yu; Chuai, Yahui; Wang, Yang; Wang, Yingzhi (Frontiers in Chemistry, 2022)
Photons trapped in the form of waveguide (WG) modes associated with the organic/organic interface and in the form of surface plasmon polariton (SPP) modes associated with the metallic electrode/organic interface result in a large energy loss in organic light-emitting devices (OLEDs).Introducing gratings onto the metallic electrode is especially crucial for recovering the power lost to the associated SPP modes.In our research, we demonstrate the efficient outcoupling of SPP modes in TE mode by 2D grating，which can not excited in 1D grating OLED. This cause a 62.5% increase in efficiency from 2D grating OLED than 1D grating OLED.The efficient outcoupling of the WG and SPP modes is verified by the numerical simulation of both the emission spectra and the field distribution.